Liquid-metal-based metasurface for terahertz absorption material: Frequency-agile and wide-angle - Song, Qing Hua (2017)
Terahertz metasurface absorption materials, which absorb terahertz wave through subwavelength artificial structures, play a key role in terahertz wave shielding and stealth technology, etc. However, most of the metasurface absorption materials in terahertz suffer from limited tuning range and narrow incident angle characteristics. Here, we demonstrate a liquid-metal-based metasurface through microfluidic technology, which functions as a terahertz absorption material with broadband tunability and wide-angle features. The proposed terahertz metasurface absorption material exhibits an experimental tuning range from 0.246 THz to 0.415 THz (the tuning range of central frequency reaches 51.1%), and the tuning range maintains at high level with wide-angle response up to 60°.